Faculty Satisfaction with Pay and Other Job Dimensions Under Union and Nonunion Conditions - Gómez‐Mejía, Luis R.; Balkin, David B. (Academy of Management Journal, 1984)
This study examines the relationship of faculty unionism on satisfaction with pay and other job dimensions. Union faculty were more satisfied with their pay than were nonunion faculty. Other significant determinants of faculty pay satisfaction were pay level, tenure, job experience, and sex. With the exception of pay, unionization was unrelated to other dimensions of job satisfaction.